SOSIALISASI POLA HIDUP SEHAT DAN BERSIH DITENGAH PANDEMI - Windiarti Pujinisa (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2021)
The KKN implementation team in Matras Village, Bangka Regency in the environmental movement carried out 4 programs, namely virtual socialization of household waste handling, distribution of fruit seeds to the surrounding community, mangrove planting and distribution of stainless pipettes. Activities were carried out in Matras Village, Bangka Regency covering the Hakok, Bukit Kuala, Matras and Jalan Laut neighborhoods. The Environmental Program aims to implement a healthy and clean lifestyle amid the pandemic. This fosters a caring attitude towards the beauty of the environment around the community.